An unusual self-assembling columnar mesogen prepared by tethering a planar naphthalenediimide acceptor to bent phenothiazine donors. Issue 1 (4th November 2021) - Thériault, Kim D.; Radford, Chase L.; Nagabhushana, Gowdaianapallya P.; Hogan, David T.; Williams, Vance E.; Kelly, Timothy L.; Sutherland, Todd C.
Abstract : Tethering of two shape mismatched donors and acceptor leads to an unusual mesogen design. Abstract : We describe a synthetic approach to achieving columnar stacked mesogens of aromatic electron donors (D) and acceptors (A) as an orthogonal strategy to segregate charge carrying channels in films. An unusual columnar liquid crystalline mesogen was designed, such that a planar naphthalenediimide acceptor flanked by two bent-shaped phenothiazine donor moieties self-assembled into a liquid crystalline phase. The use of different shapes in the D–A–D arrangement could allow segregated charge transport columns, thus limiting both intercolumnar and intramolecular D–A interactions. In solution, the mesogen showed independent optical and electronic properties of its constituent D and A components and annealed films of the columnar liquid crystalline material showed a near doubling of photocurrent generation compared to amorphousfilms.